2013
DOI: 10.1002/anie.201208593
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxorhodium/Chiral Diene Complexes as Effective Catalysts for the Asymmetric Arylation of 3‐Aryl‐3‐hydroxyisoindolin‐1‐ones

Abstract: The transition-metal-catalyzed enantioselective alkylation and arylation of imines is a versatile means of accessing a-chiral amines, which are important structural components of a number of biologically active compounds, and there have been many reports of the successful catalytic enantioselective addition of organometallic reagents to imines derived from aldehydes. [1] In contrast, the asymmetric addition of organometallic reagents to ketimines, which provides chiral a-tertiary amines, remains less developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
47
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(48 citation statements)
references
References 63 publications
1
47
0
Order By: Relevance
“…However, another asymmetric arylation of imines in the presence of arylboroxines was reported in 2013. Nishimura and co‐workers disclosed the rhodium‐catalyzed asymmetric arylation of N ‐carbonyl ketimines, obtained by the dehydration of substrates 115 . Arylboroxines worked as dehydrating reagents to generate ketimines, and arylating reagents for the subsequent arylation (Scheme ).…”
Section: Enantioselective Synthesis Of Isoindolinones By Using Transimentioning
confidence: 99%
“…However, another asymmetric arylation of imines in the presence of arylboroxines was reported in 2013. Nishimura and co‐workers disclosed the rhodium‐catalyzed asymmetric arylation of N ‐carbonyl ketimines, obtained by the dehydration of substrates 115 . Arylboroxines worked as dehydrating reagents to generate ketimines, and arylating reagents for the subsequent arylation (Scheme ).…”
Section: Enantioselective Synthesis Of Isoindolinones By Using Transimentioning
confidence: 99%
“…[16] Thus, the alkyl-substituted ketimine 1 was chosen as the substrate for our palladium-catalyzed addition reaction. Subsequently, different chiral pyridine-oxazoline-type ligands were screened (entries [1][2][3][4][5][6][7][8]. Initial solvent screening showed that catalysis in MeOH provided the most promising result (entry 1; and see the Supporting Information).…”
Section: Guoqiang Yang and Wanbin Zhang*mentioning
confidence: 99%
“…

The construction of chiral quaternary stereocenters by asymmetric catalysis remains a challenging proposition for chemists. [2] Among reactions involving the construction of chiral a-tertiary amines, [3][4][5][6][7][8][9] asymmetric addition to ketimines is a powerful strategy. [2] Among reactions involving the construction of chiral a-tertiary amines, [3][4][5][6][7][8][9] asymmetric addition to ketimines is a powerful strategy.

…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5,6,7 With an eye towards enantioselective addition of a versatile carbon nucleophile to cyclic diaryl ketimines, we envisioned enantioselective, copper-catalyzed alkynylation may provide a useful solution. Although enantioselective alkynylations of a variety of cyclic aldimines and aldiminium ions to deliver α-trisubstituted amines are known (Scheme 1, eq 1), 5a, 6, 8 only a single report of enantioselective alkynylation of a cyclic ketiminium ion exists. Maruoka has impressively shown that a Cu(Ph-PyBox)/Brønsted acid catalyst system enables alkynylation of alkyl-substituted isoquinolinium ions (Scheme 1, eq 2).…”
mentioning
confidence: 99%